The Influence of Environmental Sensitivity, Knowledge and Desire Issues (Intention To Act) with Students Behaviour as State Citizens Towards Environment - Susilowati, Diliana; Miarsyah, Mieke; Sigit, Diana Vivanti (International Journal for Educational and Vocational Studies, 2020)
Students’ behaviour as citizens towards environment is an act of voluntary and free to conduct activities that benefit the environment. This study aims to analyse the influence environmental sensitivity, knowledge of environmental issues, and intention to act, with students’ behaviour as citizens towards the environment. This research was conducted using a quantitative approach and using survey methods, and analysed using path analysis. The number of samples used as respondents was 188 students in grade XI of MIA SMAN 1 Tarumajaya Tambun Utara Kabupaten Bekasi school year of 2019/2020. Based on the results of hypothesis it can be concluded that there is a positive direct influence of environmental sensitivity towards knowledge of environmental issues. There is a direct positive influence of environmental sensitivity on the intention to act. There is a direct positive influence of environmental sensitivity on student behaviour as citizens towards environment. There is a direct positive influence of knowledge of environmental issues on the intention to act. There is a direct positive influence of knowledge of environmental issues on student behaviour as citizens towards environment. There is a direct positive influence of the intention to act on student behaviour as citizens towards environment with large path coefficients. There is an indirect positive influence of environmental sensitivity on the intention to act through the knowledge of environmental issues. There is an indirect positive influence of knowledge of environmental issues on student behaviour as citizens towards environment through the intention to act. There is an indirect positive influence of environmental sensitivity on student behaviour as citizens towards environment through the knowledge of environmental issues and the intention to act.